SYNTHESIS, MOLECULAR BIOINFORMATICS MODELLING, AND ANTIMICROBIAL EVALUATION OF SOME NOVEL OXADIAZOLE FLUOROQUINOLONE DERIVATIVES - KHAN, NAWAZ MOHAMMED; KUMAR, PAWAN; KUMAR K, HEMANTH SUDHEER; KUMAR P, BHARATH RATHNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study envisages a series of oxadiazole fluoroquinolone derivatives that were synthesized (D1–D12) with added derivatives such as phenyl, aminophenyl, amino hydroxyphenyl along with cyclopropyl, ethyl, piperazine, and imidazole. Methods: All of the newly produced molecules were characterized by infrared, 1H nuclear magnetic resonance, mass spectrometry, and elemental analysis technique and screened for docking stimulation to find out binding modes of synthesized derivatives with 3FV5, 5IMW, and 5ESE and evaluated for in vitro antimicrobial activity. Results: From this study, it was found that the compound D8 showed good antibacterial activity against Gram-positive (Staphylococcus aureus), compound D9 showed good antibacterial activity against Gram-negative (Escherichia coli), and compound D3 showed good antifungal activity against fungi (Saccharomyces cerevisiae) in comparison with standard drugs (Ciprofloxacin and fluconazole). The zone of inhibition and minimum inhibitory concentration studies was performed on synthesized compounds. Conclusion: The analogs of oxadiazole flouroquinolone are suggested to be potent inhibitors with sufficient scope for further exploration.